Rates of family history of autism and ADHD varies with recruitment approach and socio-economic status - Bazelmans, T; Scerif, G; Holmboe, K; Gonzalez-Gomez, N; Hendry, A (Wiley, 2023)
Family history (FH) of autism and ADHD is not often considered during the recruitment process of developmental studies, despite high recurrence rates. We looked at the rate of autism or ADHD amongst family members of young children (9 to 46 months) in three UK-based samples (N=1055) recruited using different methods. The rate of FH-autism or FH-ADHD was 3-9% for diagnosed cases. Rate was highest in the sample recruited through an online participant pool, which also consisted of the most socio-economically diverse families. Lower parental education and family income were associated with higher rates of FH-ADHD and lower parental education with increased FH-autism. Thus, recruitment strategies have a meaningful impact on neurodiversity and the conclusions and generalisations that can be drawn. Specifically, recruitment using crowdsourcing websites could create a sample that is more representative of the wider population, compared to those recruited through university-related volunteer databases and social media.